1993
DOI: 10.1111/j.1476-5381.1993.tb13726.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium modulatory properties of 2,6‐dibutylbenzylamine (B25) in rat isolated vas deferens, cardiac and smooth muscle preparations

Abstract: 1 In rat isolated vas deferens the new compound 2,6-dibutylbenzylamine (B25) evoked a series of repeating rhythmic contractions. Concentration-response curves constructed for this effect were bellshaped, indicating a biphasic effect for this compound. By contrast, B25 depressed heart contractility without any visible positive inotropic or chronotropic activity. 2 Experiments with tetrodotoxin, reserpine, capsaicin, a-adrenoceptor blocking compounds and other agents permit us to exclude a release of neuromediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Recently, this view has received some indirect experimental support from the observation that, when administered i.p., BZ displays a novel central hypophagic activity in mice only after pretreatment with the Bz-SSAO inhibitors B24 or MDL 72274. We have also observed that BZ induces its e ects probably by acting like the potassium channel blockers TEA or 4-aminopyridine (Pirisino et al, 1993;Banchelli et al, 2000;2001). In other investigations, it has been found that potassium channel blockers reduce food intake in mice by acting as depolarizing compounds in the brain.…”
Section: Introductionsupporting
confidence: 57%
“…Recently, this view has received some indirect experimental support from the observation that, when administered i.p., BZ displays a novel central hypophagic activity in mice only after pretreatment with the Bz-SSAO inhibitors B24 or MDL 72274. We have also observed that BZ induces its e ects probably by acting like the potassium channel blockers TEA or 4-aminopyridine (Pirisino et al, 1993;Banchelli et al, 2000;2001). In other investigations, it has been found that potassium channel blockers reduce food intake in mice by acting as depolarizing compounds in the brain.…”
Section: Introductionsupporting
confidence: 57%
“…; Rae and Calixto ; Pirisino et al. ). We try to explain this fact in Figure , where two components associated with L‐type VACCs blockers are shown: the component of channel (fast activity) and the component of signaling pathway (slow activity).…”
Section: Pharmacological Implications Of the Ca2+/camp Interaction: Rmentioning
confidence: 99%
“…In their activity, they resemble the indirectly acting compound, amphetamine, or the K q channel blocker, tetra-Ž ethylammonium Pirisino et al, 1993;Banchelli et al, . 2000 .…”
Section: Introductionmentioning
confidence: 99%